2020
DOI: 10.1016/j.jctb.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A threshold result for loose Hamiltonicity in random regular uniform hypergraphs

Abstract: Let G(n, r, s) denote a uniformly random r-regular s-uniform hypergraph on n vertices, where s is a fixed constant and r = r(n) may grow with n. An ℓoverlapping Hamilton cycle is a Hamilton cycle in which successive edges overlap in precisely ℓ vertices, and 1-overlapping Hamilton cycles are called loose Hamilton cycles.When r, s ≥ 3 are fixed integers, we establish a threshold result for the property of containing a loose Hamilton cycle. This partially verifies a conjecture of Dudek, Frieze, Ruciński andŠilei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…see[1, Remark 6.4 and Corollary 2.3]. Using Corollary 1.2 we confirm this conjecture and extend it to the case that k and r grow sufficiently slowly with n → ∞.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…see[1, Remark 6.4 and Corollary 2.3]. Using Corollary 1.2 we confirm this conjecture and extend it to the case that k and r grow sufficiently slowly with n → ∞.…”
supporting
confidence: 77%
“…When r ≥ 3 and k ≥ 2 are fixed integers, the number of Hamilton cycles in a random element of H r (k, n) has been studied by Altman et al in [1]. Let H be chosen uniformly at random from H r (k, n) and let Y be the number of loose Hamilton cycles in H. Altman et al conjectured that Proof.…”
Section: Loose Hamilton Cyclesmentioning
confidence: 99%
“…We note that Altman, Greenhill, Isaev and Ramadurai [3] recently determined the threshold for the appearance of loose Hamilton cycles in random regular r-graphs. Their results imply that for every r ≥ 3 there exists a value d 0 (which is calculated explicitly in [3]) such that if d ≥ d 0 , then G…”
Section: Theorem 37 ([10]mentioning
confidence: 82%
“…In the case of graphs, for instance, McKay and Wormald [18] showed that if certain asymptotic fomulae for the number of graphs with a given degree sequence hold, then the degree sequence of the random graph G(n, p) can be modelled by a sequence of independent binomial random variables. Furthermore, the above-mentioned hypergraph enumeration results were used in studying perfect matchings [7] and Hamilton cycles [1] in random regular hypergraphs, as well as enumerating linear hypergraphs with a given degree sequence [5]. Dudek, Frieze, Ruciński and Šileikis [8] gave a result that 'embeds' the Erdős-Rényi hypergraph inside the random regular hypergraph, thereby extending Kim and Vu's well known result for graphs to a denser case and also to hypergraphs.…”
Section: Introductionmentioning
confidence: 87%
“…The following theorem establishes that the space B k (n, m) can be used to model the degree sequence D k (n, m), as long as k is not too large. We use o (1) and ω(1) to denote functions of n tending to 0 and ∞, respectively, as n → ∞. We say that the convergence in the error term o() holds uniformly for all d in some set if there is a fixed upper bound g(n) on that error term, where g(n) → 0 as n → ∞, for all d in the given set.…”
Section: Introductionmentioning
confidence: 99%